2011
DOI: 10.1007/s10964-011-9658-2
|View full text |Cite
|
Sign up to set email alerts
|

Student Drug Testing in the Context of Positive and Negative School Climates: Results from a National Survey

Abstract: Positive school climates and student drug testing have been separately proposed as strategies to reduce student substance use in high schools. However, the effects of drug testing programs may depend on the favorability of school climates. This study examined the association between school drug testing programs and student substance use in schools with different climates. The analysis was based on a nationally representative sample of 943 high school students (48% female) ranging from 14 to 19 years of age (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In contrast, she found differences for overweight adolescents between the type of substance use and disordered eating behavior. Sznitman et al (2012) presented the results of a nationally representative sample of 943 high school student survey of student drug testing and the effects of school climates. The results of her study revealed that both male and female students in schools with positive climates reported lower levels of personal substance use.…”
mentioning
confidence: 99%
“…In contrast, she found differences for overweight adolescents between the type of substance use and disordered eating behavior. Sznitman et al (2012) presented the results of a nationally representative sample of 943 high school student survey of student drug testing and the effects of school climates. The results of her study revealed that both male and female students in schools with positive climates reported lower levels of personal substance use.…”
mentioning
confidence: 99%
“…Of the significant literature contributions previously noted,(1,6–11) only one study examined associations separately for marijuana and other illicit drugs. (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Those early findings were replicated in the current study and found to be significant with inclusion of 14 years of data. Literature on SDT efficacy generally indicates little association with illicit drug use among the general population(1,67,9) with some evidence for targeted student populations(79) for marijuana alone or in combination with other illicit drugs. In the current study, the higher predicted probabilities of OTM use associated with having various types of SDT were modest—ranging from 1 to 2 percentage points across high school SDT types and population groups, compared with a modest 3 to 4 percentage point reduction in high school marijuana use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a number of alcohol and drug interventions have targeted the school climate and generally been equally effective for both boys and girls (Oelsner et al, 2011; Sznitman, Dunlop, Nalkur, Khurana, & Romer, 2011). In the present study, several two-way interactions between peer victimization and supportive social relationships were identified.…”
Section: Discussionmentioning
confidence: 99%